2022
DOI: 10.1088/1755-1315/1024/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dryer Type on the Characteristics of Egg Flour from Frozen Eggs

Abstract: Drying process is one of the most important factors in the processing of dehydrated egg flour. Drying affect the characteristics of resulted egg flour and influence duration of the egg flour processing. Egg flour can be processed from fresh eggs or eggs that have been stored in the freezer/frozen eggs. Dehydrated egg flour has many advantages such as increase shelf life without reducing nutritional value, reduce the volume, and expands marketing reach. The aim of the study was to find out the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Regarding the standard moisture content for egg yolk powder in Indonesian, it was only available for white egg powder (SNI 01-4323-1996), but for whole and egg yolk powder were not available. However, several researcher reported that the maximum water content of egg flour is 5% [12] based on the imported standard for egg flour. Moreover, according to Koç et al [7], egg flour has a water content of 3-6%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the standard moisture content for egg yolk powder in Indonesian, it was only available for white egg powder (SNI 01-4323-1996), but for whole and egg yolk powder were not available. However, several researcher reported that the maximum water content of egg flour is 5% [12] based on the imported standard for egg flour. Moreover, according to Koç et al [7], egg flour has a water content of 3-6%.…”
Section: Resultsmentioning
confidence: 99%
“…This also occurred to a* and b* values which exhibited subtle variations, potentially indicating slight alterations in color hue and intensity due to Maillard reactions induced by the drying process. According to Hayuningtyas [12], the difference in drying treatment results in the interaction of different melanoidin pigment formation due to the the Maillard reaction. In this result, it was shown that the L* value decreased with the increase in steam pressure, indicating that the intensity of the brown color was higher.…”
Section: Resultsmentioning
confidence: 99%
“…Storage of dry egg flour products can be used at any time to make various foods and other purposes (Soekarto, 2013). Based on Hayuningtyas et al (2022), stated that the use of egg flour has advantages including being able to increase the nutritional needs of children and the potential for its use as an alternative protein source for ready-to-use therapeutic foods (RUTF). Apart from that, egg flour can be used in making cakes, custard, noodles and various cotton candies (Asghar and Abbas, 2012).…”
Section: Introductionmentioning
confidence: 99%